2018
DOI: 10.1108/pijpsm-08-2017-0091
|View full text |Cite
|
Sign up to set email alerts
|

The importance of external stakeholders for police body-worn camera diffusion

Abstract: Purpose The diffusion of innovations paradigm suggests that stakeholders’ acceptance of a police innovation shapes how it spreads and impacts the larger criminal justice system. A lack of support by external stakeholders for police body-worn cameras (BWCs) can short-circuit their intended benefits. The purpose of this paper is to examine the perceptions of BWCs among non-police stakeholders who are impacted by the technology as well as how BWCs influence their daily work processes. Design/methodology/approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 19 publications
3
47
1
3
Order By: Relevance
“…In the case of body-worn cameras, this technology addresses a need for police agencies who seek to improve transparency and community relations in an environment that has been critical of the police (Coudert et al, 2015;Cubitt et al, 2017;Harris, 2010;Tankebe & Ariel, 2016;White, 2014). Research suggest that citizens are generally in favor of police body-worn cameras whether they are community stakeholders or "frequent-flyers" (Taylor, Lee, Willis, & Gannoni, 2017;Todak, Gaub, & White, 2018) as the presence of the cameras (if recording) make citizen encounters more transparent and thus can help ensure that individual, citizen rights are protected (Koen et al, 2018;White et al, 2017).…”
Section: The Diffusion Of Body-worn Camerasmentioning
confidence: 99%
“…In the case of body-worn cameras, this technology addresses a need for police agencies who seek to improve transparency and community relations in an environment that has been critical of the police (Coudert et al, 2015;Cubitt et al, 2017;Harris, 2010;Tankebe & Ariel, 2016;White, 2014). Research suggest that citizens are generally in favor of police body-worn cameras whether they are community stakeholders or "frequent-flyers" (Taylor, Lee, Willis, & Gannoni, 2017;Todak, Gaub, & White, 2018) as the presence of the cameras (if recording) make citizen encounters more transparent and thus can help ensure that individual, citizen rights are protected (Koen et al, 2018;White et al, 2017).…”
Section: The Diffusion Of Body-worn Camerasmentioning
confidence: 99%
“…Also using a diffusion of innovations framework, Todak et al (2018) conducted focus groups and interviews with a range of stakeholders impacted by the adoption of BWCs in Spokane (WA) and Tempe (AZ). Stakeholders voiced reservations about BWCs based on their positions in the community.…”
mentioning
confidence: 99%
“…BWCs are now part of policing and we can expect that they are here to stay. Research demonstrates that both police and citizens support the use of BWCs (Gaub et al, 2020;McClure et al, 2017;Todak et al, 2018;White & Malm, 2020). However, supporting their use is different than supporting the release of BWC footage.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, with a few exceptions (Ariel, Farrar, & Sutherland, 2015;White et al, 2018), most studies have demonstrated that officers wearing BWCs received significantly fewer complaints than officers not wearing them (Ariel et al, 2017;Braga, Sousa, Coldren, & Rodriguez, 2018;Katz et al, 2014). On the other hand, community surveys indicate that the public is supportive of agencies outfitting their officers with BWCs because they see it as a way to hold police more accountable for disparities in stops, arrests, and uses of force (Sousa et al, 2018;Todak et al, 2018). Interestingly, then, both parties see BWCs as a way to hold the other more accountable (White & Malm, 2020).…”
mentioning
confidence: 99%